Uji Organoleptik Yoghurt Drink Dengan Penambahan Ekstrak Buah Jeruk Manis (Citrus Sinensis) - Sudirman, Sudirman; Irmawaty, Irmawaty; Astati, Astati; Mursidin, Mursidin (Anoa: Journal of Animal Husbandry, 2025)
This study aims to determine the effect of the addition of sweet orange fruit extract (Citrus sinensis) on yogurt drink with organoleptic tests. The research method used a Complete Random Design (RAL) with 4 treatments and 3 replicates, namely P0: no sweet orange extract (Citrus sinensis), P1: 5% sweet orange extract (Citrus sinensis), P2: 7% sweet orange extract (Citrus sinensis), P3: 9% sweet orange extract (Citrus sinensis). The parameters tested in this study were (color, aroma, taste, texture and level of liking). Data analysis used Analysis of Variance (ANOVA) and the Smallest Real Difference (BNT) test. The results showed that the addition of sweet orange extract (Citrus sinensis) at different levels had a very real effect (P<0.01) on color, aroma, taste and level of liking while on texture had a real effect (P<0.05). The highest organoleptic test on color, aroma, taste, texture and preference level was obtained in P3 treatment: (9%). While the lowest in the P0 treatment: without the addition of sweet orange extract (Citrus sinensis). The addition of sweet orange fruit extract with treatment (9%) is preferred by consumers.